Trace element partitioning and substitution mechanisms in calcium perovskites - Corgne, A; Wood, B (2005)
We have determined the partition coefficients of a large number of trace elements between CaTiO 3 perovskite and anhydrous silicate melts at atmospheric pressure and 3 GPa. Determination of the concentration limits of Henry's law behaviour in the CaO-Al 2 O 3-SiO 2-TiO 2 system reveals that the incorporation of rare earth elements (REE) and tetravalent large ion lithophile elements (LILE 4+ such as U and Th) at the Ca-site of CaTiO 3 perovskite occurs with charge compensation through Ca-vacancy formation rather than by coupled substitution of Al for Ti. When melt composition is varied, we find that partition coefficients for REE and Th are strong functions of the CaO content of the melt. The observed trends are in excellent agreement with those predicted from the Ca-vacancy model. Given that they adopt the same crystal structure and have similar trace element partitioning behaviour, CaTiO 3 perovskite and the deep mantle phase CaSiO 3 perovskite can be considered analogous to one another. When the analogy is pursued in detail, we find that partitioning into both phases follows the composition-dependence predicted by the Ca-vacancy model. Thus, substitution of REE, U 4+ and Th into CaSiO 3 in the lower mantle also occurs with Ca-vacancy formation to balance charge. Furthermore when 2+, 3+ and 4+ partition coefficients for both phases are plotted as functions of CaO melt content, the trends for CaSiO 3 and CaTiO 3 appear to be continuous. This surprising result means that partitioning into Ca-perovskite is independent of pressure and temperature and also of whether or not the host is CaSiO 3 or CaTiO 3. One implication is that CaSiO 3 crystallising from a peridotitic magma ocean may have partition coefficients for Th and U up to about 400. Crystallisation and sequestration of as little as 0.25 volume% of this phase in the lower mantle early in earth history would make a significant contribution to current mantle heat production. © Springer-Verlag 2005.